Physicochemical characterization of Artisanal Minas cheese from the cerrado micro-region (Research, Society and Development, 2022)
This work aimed to make the physical-chemical characterization of Minas Artesanal cheese from a producer in the municipality of Cruzeiro da Fortaleza, in the Cerrado micro-region. Minas Artesanal cheese is distinguished from other cheeses produced in Brazil by the addition of “pingo” in raw milk and manual pressing, which provide unique characteristics in aroma, flavor, odor and texture. The physical-chemical analyzes guarantee the producer and the consumer the safety of the food and its compositions, guaranteeing that the product complies with the standards described in the legislation, thus avoiding fraud or adulteration of products that can be highly harmful to human health. A unit of a batch of Minas Artesanal do Cerrado Cheese, from the municipality of Cruzeiro da Fortaleza, with 03 days of manufacture was used. The proximate composition was characterized on a wet basis, considering moisture, lipids, proteins and ash. In addition, titratable acidity and presence of starch were evaluated. It was observed that the average percentages of moisture and ash found were 44.71% and 3.195%, respectively; while the value verified for lipids was 27.66%. As for the protein, a value of around 21.33% was observed. The presence of starch was negative and the average titratable acidity found in lactic acid was 0.225%. It was concluded that the analyzed cheese meets the minimum parameters determined by Brazilian legislation, highlighting that the differences found in relation to the literature are mainly due to external and non-standard factors.